Soziativa im Deutschen und Polnischen - Bzdęga, Andrzej Z (Studia Germanica Posnaniensia, 2018)
The author describes and then compares the existing means of expressing sociativeness in German and Polish, formative (e.g. nouns in Ge-, nouns and verbs in mit- and ko/n/- in German, expressions with wspól- in Polisb), as well as lexical and syntactic (e.g. nouns of the type Gefährte, Geselle, Genosse, phrases of the kind zu zweit, zu zweien in German nouns of the type towarzysz, kolega and phrases of the kind we dwoje, we dwójkę in Polish). The author discusses in more detail the so called sociative of the kind of German selbander, selbdritt, Polisb samowtór, samotrzeć (cf. English the two of you/ us/ them), and especially their occurrence in the old legal parlance.